Food and Government; Study of Food Safety Issues in Indonesia - Tendy, Tendy; Purwanti, Silviana (Budapest International Research and Critics University, 2021)
The government has a role that can contribute negatively to the emergence of food security problems. As in Sen's analysis, undemocratic government is one of the causes of national food insecurity. This statement uses the term Indonesian territory and not the state of Indonesia, and uses the term famine event and not a famine. This is because the biggest event occurred in the 1800s and not on a national scale that Indonesia had several times of famine. For this reason, it is important for state administrators to ensure the availability and equitable distribution of food to individuals. This realization must also include the availability of food that is good in quality and quantity, safe, diverse, nutritious, and affordable and does not conflict with religion, belief, and community culture, and is sustainable.